Morpholino Antisense Oligomers as a Potential Therapeutic Option for the Correction of Alternative Splicing in PMD, SPG2, and HEMS - Stephanie Tantzer; Karen Sperle; Kaitlin Kenaley; Jennifer Taube; Grace M. Hobson (Elsevier, 2018)
DNA variants of the proteolipid protein 1 gene (PLP1) that shift PLP1/DM20 alternative splicing away from the PLP1 form toward DM20 cause the allelic X-linked leukodystrophies Pelizaeus-Merzbacher disease (PMD), spastic paraplegia 2 (SPG2), and hypomyelination of early myelinating structures (HEMS). We designed a morpholino oligomer (MO-PLP) to block use of the DM20 5' splice donor site, thereby shifting alternative splicing toward the PLP1 5' splice site. Treatment of an immature oligodendrocyte cell line with MO-PLP significantly shifted alternative splicing toward PLP1 expression from the endogenous gene and from transfected human minigene splicing constructs harboring patient variants known to reduce the amount of the PLP1 spliced product. Additionally, a single intracerebroventricular injection of MO-PLP into the brains of neonatal mice, carrying a deletion of an intronic splicing enhancer identified in a PMD patient that reduces the Plp1 spliced form, corrected alternative splicing at both RNA and protein levels in the CNS. The effect lasted to post-natal day 90, well beyond the early post-natal spike in myelination and PLP production. Further, the single injection produced a sustained reduction of inflammatory markers in the brains of the mice. Our results suggest that morpholino oligomers have therapeutic potential for the treatment of PMD, SPG2, and HEMS. Keywords: Pelizaeus-Merzbacher disease, PMD, spastic paraplegia 2, SPG2, hypomyelination of early myelinating structures, HEMS, antisense RNA, alternative splicing, morpholino oligomer, treatment